Above the bottom line : an introduction to business ethics - Solomon, Robert C.
ABOVE THE BOTTOM LINE focuses on the issues of the individual in the business environment, rather than focusing on large-scale, ethical decision making. Business is defended as a necessary and valuable component of contemporary life, a range of entrepreneurial ventures that should be approached in a principled, thoughtful, and honest manner. Looking at the importance of corporate culture, students are given direction in making personal and professional decisions at work, relating these to the concepts of social responsibility, employer and employee rights, whistle-blowing, corporate governance, bankruptcy, and many other timely business issues